ADMISSION SYSTEMS IN ISLAMIC SECONDARY SCHOOLS: A COMPARATIVE STUDY BASED ON STUDENTS ACHIEVEMENT AND CONSENT - Endah Winarti; Binti Nasukah; Raheb Sulaiman O Alturki (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2026)
Admission policies are increasingly recognized as strategic tools through which educational institutions project their values and define desired student profiles. While extensive research has examined admissions based on academic achievement, equity, or socio-economic background, little attention has been paid to the affective and aspirational dimensions of student selection, particularly in non-Western and faith-based contexts. This study addresses that gap by exploring how two kinds of Islamic secondary schools in Indonesia (Madrasah and Pesantren), construct and operationalize their admission logics. Employing a qualitative comparative case study design, data were gathered through interviews, observations, and document analysis. Findings reveal two divergent approaches: Madrasah privileges measurable academic excellence, while Pesantren emphasizes student consent, defined as a student’s expressed willingness to undertake a long-term educational commitment. These criteria reflect not only institutional visions but also produce distinct graduate outcomes. By introducing student consent as a novel analytical construct, this study expands existing frameworks of admission policy. The findings offer theoretical insight into the ideological dimensions of student selection and practical guidance for designing mission-aligned admission strategies. Keywords: Admission Policies; Student enrollment; Islamic Education; Students Consent; Students achievement; secondary school.       Abstrak Kebijakan penerimaan siswa semakin dipahami sebagai alat strategis bagi lembaga pendidikan untuk menampilkan nilai-nilai yang mereka anut sekaligus menentukan profil siswa yang diharapkan. Selama ini, banyak penelitian membahas sistem penerimaan yang bertumpu pada prestasi akademik, aspek keadilan, atau latar belakang sosial ekonomi. Namun, perhatian terhadap dimensi afektif dan aspiratif dalam proses seleksi siswa masih sangat terbatas, terutama dalam konteks non-Barat dan lembaga pendidikan berbasis keagamaan. Penelitian ini mengisi kekosongan tersebut dengan mengkaji bagaimana dua jenis lembaga pendidikan Islam jenjang menengah di Indonesia (Madrasah dan Pesantren), merancang dan menerapkan alur logika penerimaan siswa mereka. Menggunakan desain studi kasus komparatif dengan pendekatan kualitatif, data dikumpulkan melalui wawancara, observasi, dan analisis dokumen. Hasil penelitian menunjukkan adanya dua pendekatan yang berbeda. Madrasah lebih mengutamakan keunggulan akademik yang dapat diukur, sementara Pesantren menekankan kesediaan siswa (student consent), yang dimaknai sebagai kemauan siswa untuk menjalani komitmen pendidikan jangka panjang. Perbedaan kriteria ini tidak hanya mencerminkan visi kelembagaan masing-masing sekolah, tetapi juga melahirkan karakter lulusan yang berbeda. Dengan memperkenalkan konsep student consent sebagai konstruk analitis baru, penelitian ini memperluas kerangka kajian tentang kebijakan penerimaan siswa. Temuan ini memberikan kontribusi teoretis dalam memahami dimensi ideologis dari proses seleksi siswa, sekaligus menawarkan panduan praktis bagi lembaga pendidikan dalam merancang sistem penerimaan yang selaras dengan misi. Kata kunci: Kebijakan Penerimaan; Pendaftaran Siswa; Pendidikan Islam; Persetujuan Siswa; Prestasi Siswa; Sekolah Menengah.